Perlindungan dan Pendampingan Hukum Kekayaan Intelektual dalam Pendaftaran Merek Dagang bagi Pelaku UMKM di Desa Cililin - Gunawan, Gunawan; Putra, Egi Rizki Maulana (Fakultas Syariah INSURI Ponorogo, 2023)
The existence of MSMEs is considered to have a very important role in the economy in Indonesia because in its expansion there are more and more MSMEs activists in Indonesia and every year it increases quite significantly, especially in the Cililin village itself, with the presence of MSMEs, many jobs are open to the community. Trademark registration for MSME business actors is now very important, because there are many cases of trademark dispute lawsuits that occur in MSME business actors, this is very detrimental for business actors, but there is a lack of public understanding of registration of intellectual trademark rights which is considered difficult to register, even though in reality. This study aims to provide insight into the importance of registering trademarks and also to help SMEs to be able to register their trademarks into the system of the Directorate General of Intellectual Property. This study used the direct service observation method and data collection using interview, observation, and documentation techniques. The condition of MSMEs in the Cililin Village area itself still lacks support or assistance from local government officials where there are still many MSMEs, almost 70% have not registered their own trademark rights due to the lack of support or encouragement from the local government to socialize the importance of registering trademark rights. However, with this research, researchers helped MSME activists who did not understand the online application procedure, as well as the limited time that MSME activists had because apart from being entrepreneurs, MSME activists also had to be housewives. By assisting MSME activists in registering their trademarks, this activity can provide a number of benefits to MSME activists, including providing encouragement, support and legal protection for the businesses they own.